Open Bristow Versus Open Latarjet for Anterior Shoulder Instability in Rugby Players: Radiological and Clinical Outcomes. Issue 5 (12th May 2022) - Tanaka, Makoto; Hanai, Hiroto; Kotani, Yuki; Kuratani, Kosuke; Nakai, Hidekazu; Kinoshita, Shuma; Hirose, Takehito; Hayashida, Kenji
Background: Coracoid transfer is a reliable method for managing anterior shoulder instability in athletes who play contact sports; however, differences between the Bristow and Latarjet procedures are unclear. Purpose: To compare clinical outcomes and rates of bone union and bone resorption of the coracoid process between the open Bristow and open Latarjet procedures in rugby players. Study Design: Cohort study; Level of evidence, 3. Methods: Rugby players who underwent an open Bristow or an open Latarjet procedure were retrospectively reviewed for anterior shoulder instability, and 66 shoulders in the Bristow group and 35 in the Latarjet group were included. Graft union and resorption were evaluated using computed tomography at 3 months to 1 year postoperatively. Patient-reported outcome measures (American Shoulder and Elbow Surgeons score, Rowe score, and satisfaction rate) were obtained at a mean follow-up of 74 months (range, 45-160 months) for Bristow and 64 months (range, 50-76 months) for Latarjet procedures. Recurrence and the rate of return to play (RTP), frequency of pain after RTP, and retirement rate after RTP were also assessed. Results: In 97.1% of the Latarjet procedure cases, bone union of the coracoid was achieved at 3 months postoperatively; however, bone union was achieved in only 72.7% of the Bristow procedure cases at 6 months postoperatively. Bone resorption of the coracoid process occurred in 6.1% of shoulders after the Bristow procedure, whereas 100% of shoulders showed bone resorption after the Latarjet procedure. No statistical differences were found in outcome scores between the 2 procedures. Subluxation and persistent pain after returning to sports were identified at a significantly higher rate in the Latarjet group (5 shoulders [14%] and 9 shoulders [26%], respectively) than in the Bristow group (2 shoulders [3%] and 2 shoulders [3%]) ( P = .0471 and P = .001, respectively). Conclusion: The Latarjet procedure had an advantage in the early and high rate of bone union but was at a disadvantage in bone resorption compared with the Bristow procedure. Subluxation and pain after returning to sports were more frequent in patients who underwent the open Latarjet procedure than in those who underwent the open Bristow procedure.